Analysis of the Effects of the Work Environment and Workload on Employee Performance - Rahmawati; Asmawiyah; Hidayat (Economy, Business, Finance, Accounting & Management Journal, 2025)
Employee productivity is one of the key factors determining an organization’s success in achieving its business objectives. However, productivity levels are often influenced by various internal factors, particularly work motivation and job satisfaction. Highly motivated employees tend to demonstrate greater enthusiasm, commitment, and better performance, while job satisfaction can enhance loyalty and the quality of work output. This study aims to analyze the role of work motivation and job satisfaction in improving employee productivity. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to employees within an organization. The data obtained were analyzed using multiple linear regression to test the influence of each variable on work productivity. The results indicate that work motivation and job satisfaction have a positive and significant effect on employee productivity, both partially and simultaneously. Work motivation was found to drive improvements in individual performance, while job satisfaction fosters a work environment that supports the achievement of organizational goals. Thus, it can be concluded that enhancing work motivation and job satisfaction is an effective strategy for boosting employee productivity and supporting the organization’s sustained success